2010
DOI: 10.5424/fs/2010191-01163
|View full text |Cite
|
Sign up to set email alerts
|

Forestry applications of ground-penetrating radar

Abstract: Ground-penetrating radar (GPR) is a geophysical and close-range remote sensing technique based on the use of radar pulses to obtain cross-section images of underground features. This method is characterized by the transmission of an electromagnetic short length pulse (1-2 ns), presenting a centre frequency ranging from 10 MHz to 2.5 GHz. The principles of GPR operation are based on the ability of low frequency radar waves to penetrate into a non-conductive medium, usually subsoil, but also walls, concrete or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…Hruška et al (1999) first applied GPR technique for coarse root detection and claimed that GPR was an appropriate tool for coarse root mapping. The major interests of using GPR to detect coarse root thus far include: 1) coarse root mapping (e.g., Hruška et al 1999;Čermák et al 2000;Wielopolski et al 2000;Stokes et al 2002;Cox et al 2005;Samuelson et al 2008;Zenone et al 2008;Schoor and Colvin 2009;Leucci 2010;Bassuk et al 2011); and 2) coarse root biomass and diameter estimation (e.g., Butnor et al 2001Butnor et al , 2003Barton and Montagu 2004;Butnor et al 2005;Cox et al 2005;Stover et al 2007;Butnor et al 2008;Samuelson et al 2008;Dannoura et al 2008;Hirano et al 2009;Lorenzo et al 2010;Cui et al 2011). In what follows, each of the applications is comprehensively reviewed.…”
Section: Applying Gpr For Coarse Root Detection and Quantificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hruška et al (1999) first applied GPR technique for coarse root detection and claimed that GPR was an appropriate tool for coarse root mapping. The major interests of using GPR to detect coarse root thus far include: 1) coarse root mapping (e.g., Hruška et al 1999;Čermák et al 2000;Wielopolski et al 2000;Stokes et al 2002;Cox et al 2005;Samuelson et al 2008;Zenone et al 2008;Schoor and Colvin 2009;Leucci 2010;Bassuk et al 2011); and 2) coarse root biomass and diameter estimation (e.g., Butnor et al 2001Butnor et al , 2003Barton and Montagu 2004;Butnor et al 2005;Cox et al 2005;Stover et al 2007;Butnor et al 2008;Samuelson et al 2008;Dannoura et al 2008;Hirano et al 2009;Lorenzo et al 2010;Cui et al 2011). In what follows, each of the applications is comprehensively reviewed.…”
Section: Applying Gpr For Coarse Root Detection and Quantificationmentioning
confidence: 99%
“…They concluded that many aspects of GPR hardware, visualization software, and signal processing methods need to be improved before precise 3D root system images could be reconstructed from radargrams. Due to the difficulty of root 3D architecture reconstruction, some studies (e.g., Lorenzo et al 2010;Leucci 2010) attempted to apply GPR to resolve root-zone (i.e., the region of soil located in and around the root system) in 2D/3D rather than accurately locate single coarse root. In these studies, GPR was used to scan root systems in a grid (consisting of different parallel lines in both x and y directions).…”
Section: Coarse Root Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…When the pulses encounter subsurface interfaces or boundaries with different dielectric constants, the reflections are different. The internal defects have a different dielectric constant from that of surrounding wood [5]. Thus, the research is able to deduce the location of the internal defects of tree and make the defects layered recognition based on the properties.…”
Section: Gpr Principlementioning
confidence: 97%
“…In recent years, scholars also gradually take GPR for trees detection seriously. Studies pointed out that these anomalies could be associated the inner discontinuities between the bark and the internal trunk and lower velocities correspond to living trees, while higher velocities are associated with timber [5]. Other studies located the position of internal defects and the algorithm for identifying the defects in wooden logs using GPR [6]; some others showed relations between relative permittivity and moisture content of the different wood samples [7].…”
Section: Introductionmentioning
confidence: 99%